Colton Christmas conspiracy - Childs, Lisa (Harlequin romantic suspense, 2020)
"Neil Colton and Mayor Elise Willis loved and lost each other long ago...but desire and danger soon reunite them this holiday season. In the aftermath of an attack on both their lives, Elise reveals that--thanks to one reckless night--she's pregnant with Neil's baby. Nothing will prevent the lawyer from protecting the woman he loves and the child he's always wanted... Even if it means losing his own life" --Amazon.